Penerapan Fungsi Manajemen dalam Pengelolaan Perpustakaan Madrasah Aliyah (Studi Kasus di Perpustakaan MAN 2 Palembang) - Rhoni Rodin (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
The purpose of this study was to analyze how the application of management functions in the madrasa library, especially in the MAN 2 Palembang library. The research method uses a descriptive approach with qualitative analysis. Data collection techniques used were observation, interview and document study. The results showed that in general the MAN 2 Palembang Library had implemented a management function in library management. The management functions applied include planning, organizing, avtuating and supervising. In general, the management of the school library at the MAN 2 Palembang Library is good enough, but there are still some aspects that must be fixed. MAN 2 Palembang library management planning process is more cornered to user education which can be carried out in the new school year which is carried out simultaneously with the student orientation period. Organizing in the management of school libraries with school libraries in general. The organization includes the form of organizational structure and the division of work of each library staff. The mobilization process related to the leadership process is carried out by the school principal. Mobilization related to job description is carried out with instructions from the Head of Library. Although there are no binding supervision standards, as a form of responsibility the head of the library makes a report every 6 months and the end of the school year is addressed to the principal. However, there are still some obstacles that hamper the process of management in the library; 1) The availability of computers and internet services is still not available to support better management and library services 2) Knowledge of the classification of Islam that should have been determined in Islamic-based school libraries.